Improvement of rural soil properties and states by biomass carbon under the concept of sustainability: A research progress - Yang, Yuchi (Frontiers in Chemistry, 2022)
Biomass carbon is a highly aromatic carbonaceous solid obtained by thermochemical reaction of biomass raw materials. It is frequently used in the research and application of soil properties and states improvement. Biomass carbon has abundant porous structure, high specific surface area and surface functional groups. After being applied to the soil, it has a significant impact on manipulating the physichemical properties of the soil, enhancing the microbial environment and remediating soil pollutants, which is conducive to the resource utilization of agricultural wastes and the long-term preservation of the environment. Based on 328 moderately to highly relevant literatures on biomass carbon and rural soil property improvement since 2010, this paper reviewed the contemporary research progress of biomass carbon application in soil property improvements utilizing the concept of sustainable development. In order to provide beneficial illumination for the complete implementation of biomass carbon in improving rural soil properties, this paper primarily evaluated the principle as well as mechanism of promoting sustainable soil properties. It tends to prospect the application and development aspirations of biomass carbon in soil ecological restoration, crop growth, development.